Plasmonic nanoantennas with liquid crystals for nanocrystal fluorescence enhancement and polarization selectivity of classical and quantum light sources. (2nd November 2017) - Lukishova, Svetlana G.; Liapis, Andreas C.; Zhu, Huiqing; Hebert, Eric; Kuyk, Kevin; Choudhary, Saumya; Boyd, Robert W.; Wang, Ziyue; Bissell, Luke J.
ABSTRACT: We discuss plasmonic nanoantennas for emitter fluorescence enhancement and wavelength tunability of plasmonic resonance using liquid crystals. The results of numerical modeling of a plane wave scattered by bowtie nanoantennas in isotropic liquid crystal media with different refractive indexes are presented for two plasmonic materials. Experimental results are reported on fabricated gold bowtie nanoantenna arrays by high-precision electron-beam lithography. Photon antibunching from nanocrystal quantum dot within a bowtie nanoantenna gap was obtained, proving nonclassical behavior of light from such a source. In addition, the first results towards gap/patch nanoantennas with single emitters in liquid crystal hosts as well as photon antibunching are reported for nanodiamonds with NV-color-centers dispersed in nematic liquid crystal hosts. Depending on nanocrystal concentration our results can find applications in displays, organic light-emitting diodes, microlasers, and single photon sources for secure quantum communication.